Some Measures of Core Inflation and Their Evaluations in Nepal - Shrestha, Prakash Kumar (NRB Economic Review, 2006)
This paper measures core inflation and evaluates their performance in Nepal. Concept of core inflation and survey of methodologies as well as international experiences and empirical evidence have been reviewed and analysed before measuring the core inflation in Nepal. An existence of asymmetric price distribution necessitates the alternative measure of inflation in place of traditional CPI-based headline inflation. Ultimately, by using exclusion method and stochastic measures, nine different types of core inflations have been computed. Empirical results show that core inflations perform better than the headline inflation in several aspects such as having less volatility, highly relating to money supply growth, and capturing the permanent component of headline inflation. Better core inflation is selected with the help of different performance criteria such as observing statistical properties, tracking trend inflation, finding the relationship with money supply, and the analysing the ability of capturing permanent component and forecasting capacity. However, no single core measure performs better in all aspects. Hence, a set of core inflation measures, namely exclusion based, weighted median and trimmed mean should be analysed in conducting the monetary policy in Nepal.